Crystal Structure and High-Temperature Thermoelectric Properties of the Mo3-x Ru (x) Sb-7 Compounds - Candolfi, C; Leszczynski, J; Masschelein, P; Chubilleau, C; Lenoir, B; Dauscher, A; Guilmeau, E; Hejtmanek, J; Clarke, S; Smith, R (2010)
Zintl phases are currently receiving great attention for their thermoelectric potential typified by the discovery of a high ZT value in Yb 14MnSb 11-based compounds. Herein, we report on the crystallographic characterization via neutron and x-ray diffraction experiments, and on the thermoelectric properties measured in the 300 K to 1000 K temperature range, of Mo 3Sb 7 and its isostructural compounds Mo 3-x Ru x Sb 7. Even though Mo 3Sb 7 displays rather high ZT values given its metallic character, the partial substitution of Mo by Ru substantially improves its thermoelectric properties, resulting in a ZT value of ∼0.45 at 1000 K for x = 0.8. © 2009 TMS.